2013
DOI: 10.1021/jp408717x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lithium Bis(oxalate)borate Electrolyte Additive on the Performance of High-Voltage Spinel/Graphite Li-Ion Batteries

Abstract: The impact of lithium bis(oxalate)borate (LiBOB) electrolyte additive on the performance of full lithium-ion cells pairing the high-voltage spinel cathode with the graphite anode was systematically investigated. Adding 1 wt % LiBOB to the electrolyte significantly improved the cycle life and Coulombic efficiency of the full-cells at 30 and 45 °C. As the LiBOB was preferentially oxidized and reduced compared with LiBOB-free electrolyte during cycling, their relative contributions to the improved capacity retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
153
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(157 citation statements)
references
References 43 publications
4
153
0
Order By: Relevance
“…[14][15] Both of these basic compounds, can trap dissolved transition metal ions in the electrolyte by forming coordinated complexes, thus inhibiting the reductive deposition of these metal ions onto negative electrode surface. Also, as Lewis bases, they have the potential to neutralize acidic gaseous compounds like PF 5 , HF and CO 2 generated by electrolyte (LiPF 6 and organic carbonates) decomposition, thus reducing gas generated during cycling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15] Both of these basic compounds, can trap dissolved transition metal ions in the electrolyte by forming coordinated complexes, thus inhibiting the reductive deposition of these metal ions onto negative electrode surface. Also, as Lewis bases, they have the potential to neutralize acidic gaseous compounds like PF 5 , HF and CO 2 generated by electrolyte (LiPF 6 and organic carbonates) decomposition, thus reducing gas generated during cycling.…”
mentioning
confidence: 99%
“…Zuo et al reported, by adding 1.0 -2.0 wt% of LiBF 4 into LiPF 6 -based electrolyte, significant improvements in capacity retention and interfacial impedance of graphite/LiNi 0.5 Mn 0.3 Co 0.2 O 2 pouch cells cycled between 3.0 and 4.5 V. 16 They state in their conclusion: "On the other hand, in the presence of LiPF 6 , LiBF 4 decomposes to BF 3 , which is believed to take part in the formation of a passivation film on the LiNi 0.5 Mn 0.3 Co 0.2 O 2 cathode during high voltage operation." In addition, BF 3 , like many other electron deficient borates or boranes, is a typical Lewis-acid which could function as an anion receptor to help dissolve one of the LiPF 6 decomposition products-LiF, from the electrolyte/electrode interface.…”
mentioning
confidence: 99%
“…One of the most promising methods to improve the performance of LiNi 0.5 Mn 1.5 O 4 cathode films is via the incorporation of cathode film forming electrolyte additives that are sacrificially oxidized on the cathode surface to generate a cathode passivation layer. 7,11,12 While many different additives have been investigated, lithium bis(oxalate)borate (LiBOB) [13][14][15][16] and other lithium borates 6,7,17,18 are among the most widely investigated electrolyte additives which have been reported to improve the performance of cathodes operating at high potential. However, the borate additives have limitations and thus it is important to develop novel cathode film forming additives to improve the performance of high voltage LiNi 0.5 Mn 1.5 O 4 cathodes.…”
mentioning
confidence: 99%
“…This may not be the optimum ratio. Zuo et al 7 reported that LiBF 4 added as an additive could reduce impedance during high potential cycling and that the beneficial effects of LiBF 4 arise from the single BF 4 − ion. It is important to know which functional group, pyridine or BF 3 , has a greater impact in PBFtype additives and which functional group is more beneficial to Li-ion cell lifetime.…”
mentioning
confidence: 99%